USE OF HYALURONIC ACID PRODUCED FROM A LOCAL ISOLATE OF STREPTOCOCCUS THERMOPHILUS AS AN ANTIOXIDANT IN CRUDE SUNFLOWER OIL - Niamah, Alaa (Food and Feed Research, 2026)
Hyaluronic acid is a natural antioxidant derived from various sources, including microbial ones, and is utilised in multiple fields, including medicine, food, and cosmetics. A local isolate of Streptococcus thermophilus, cultured on whey medium, was used to produce hyaluronic acid, which was identified by the carbazole reaction, high-performance liquid chromatography (HPLC), and Fourier transform infrared (FTIR) spectroscopy. The antioxidant activity of hyaluronic acid was then evaluated by measuring the reducing power of 2,2-diphenyl-1-picrylhydrazyl (DPPH), hydrogen peroxide removal, and ferrous ion chelation, in comparison with the synthetic antioxidant BHT. It was then used as an antioxidant to preserve sunflower oil for a 90-day storage period. The results showed that the hyaluronic acid production rate was 0.598 g/L, and that a concentration of 500 µg/ml of the acid (dissolved in saline solution) was most effective in scavenging DPPH free radicals and hydrogen peroxide, with scavenging rates of 68.14% and 72.08%, respectively, while the iron ion binding rate was 81.98%. The addition of hyaluronic acid extract to crude sunflower oil resulted in lower levels of oxidation, acidity, and thiobarbituric acid during storage periods of 30, 60, and 90 days. The study also showed that sunflower oil stored in transparent containers was more susceptible to oxidation than oil stored in opaque containers. Therefore, hyaluronic acid can be used as a natural antioxidant and an alternative to synthetic preservatives to preserve oils and extend their shelf life.
Keywords: natural antioxidant; alternative antioxidant; shelf life; antioxidant activity; sunflower oil; oxidation stability